OBSTACLE DETECTION FOR CAR COLLISION AVOIDANCE USING STEREOSCOPIC - Akram Muhammad Razee, 1988-, author; Salwani Mohd. Daud, Assoc.Prof.Dr., supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2014)
Thesis